2020
DOI: 10.1007/s00508-020-01717-7
|View full text |Cite
|
Sign up to set email alerts
|

Partially ionized medical oxygen as a supplementary treatment for COVID-19

Abstract: Letter to the editor Dear Editors, we read with interest the recent report by Rowen and Robins regarding the effective treatment for "novel coronavirus" SARS-CoV with ozone therapy [1]. The authors explained the effect of ozone therapy through oxidation of the membrane glycoproteins, where thiol groups in reduced form (R-S-H) are changed to disulphide (R-S-S-H). Then, viral enzymes can become inactive when reduced thiols are oxidized. Coronavirus structure has regions rich in cysteine, which are vulnerable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The use of this method needs a special medical device and require hospitalization. Moreover, the effective time of oxygen inhalation for virus inactivation has not been estimated yet 78,79 . Clinical studies have proven that the use of O 2therapy by high-flow nasal cannula (HFNC) in patients with severe hypoxemic acute respiratory failure (hARF) caused by SARS-CoV-2 infection is a safe and effective treatment for less severe patients with SARS-CoV-2 hARF; however, the efficacy would need further assessment as part of a clinical trial 80,81 .…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…The use of this method needs a special medical device and require hospitalization. Moreover, the effective time of oxygen inhalation for virus inactivation has not been estimated yet 78,79 . Clinical studies have proven that the use of O 2therapy by high-flow nasal cannula (HFNC) in patients with severe hypoxemic acute respiratory failure (hARF) caused by SARS-CoV-2 infection is a safe and effective treatment for less severe patients with SARS-CoV-2 hARF; however, the efficacy would need further assessment as part of a clinical trial 80,81 .…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…According to recent studies, therapy with ionized oxygen might be a useful tool to treat COVID-19 patients as in vitro studies confirmed that long-term inhalation of partially positively ionized oxygen (O2+) was associated with less oxidative stress, better ability to secure airway patency and milder pulmonary inflammation response than molecular oxygen (133).…”
Section: The Supplementary Oxygenation Axismentioning
confidence: 99%